DEMOKRATİK EĞİTİM ÜZERİNE - İbrahim Özdemir (Felsefe Dünyası)
This work attempts to"underline the relevance of education for the development of democracy in the Muslim societies. To do this, it analyzes the historical development of democracy in the West, which is apparently based on the new emerging concept of man since 17th century. Then, it suggests that if Muslim societies interested in the development of democracy as a system of governance, they should develop it through education on their own cultural and historical context. It is suggests that Muslim societies should de-construct and then re-construct of the cultural and traditional heritage with a philosophical manner.